Potassium promoted Gd0.06Co catalysts for highly efficient catalytic N2O decomposition in presence of impurity gases at low temperature. (September 2022) - Xiong, Ying; Zhao, Yumei; Shan, Weijun; Feng, Xiaogeng; Cui, Junshuo; Lou, Zhenning; Shao, Guoxiang; Dong, Min; Yu, Haibiao
Abstract: In order to enhance the catalytic performance of the Gd-modified Co3 O4 catalyst (Gd0.06 Co) for the N2 O decomposition, alkali metal K was introduced as the promoter by impregnating the Gd0.06 Co powder with an aqueous solution of KNO3 (with K/Co ratios 0.01–0.05). With the doping of K, the catalytic activity over Gd0.06 Co was significantly improved and the temperature of N2 O complete decomposition was decreased from 350 °C to 300 °C. Combining the results of XPS and O2 -TPD, the superior catalytic performance of the optimum catalyst K0.025 Gd0.06 Co was mainly owing to the synergistic effect of Gd and K, which weakened the Co–O bond and endowed the catalyst surface with much more amount of oxygen vacancies. Even under the coexist of the impurity gases, such as 5 vol% O2, 100 ppmv NO and 2 vol% H2 O, the K0.025 Gd0.06 Co catalyst exhibited prominently better catalytic activity than Gd0.06 Co and K0.025 Co catalysts. Graphical abstract: Image 1 Highlights: Catalytic activity of Gd0.06 Co for N2 O was improved significantly by K. Textural structure and surface area were maintained after K impregnation. Active sites was increased from 49.36 to 266.56 μmol g −1 due to the addition of K. It exhibited superior performance in presence of impurity gases at low temperature.